Postoperative Pain Management Total Hysterectomy with Intravenous Patient-Controlled Analgesia Oxycodone: A Case Series - Muh. Nur Abadi; Alamsyah Ambo Ala Husain (HM Publisher, 2022)
Introduction: Patient-controlled analgesia (PCA) with intravenous opioids is a more efficient method to achieve better postoperative analgesia. This study aims to describe the use of patient-control analgesia in post-hysterectomy patients. Case presentation: There were two total hysterectomy postoperative patients who used PCA as postoperative pain management. Postoperatively, the first patient has given paracetamol tablets 500 mg every 6 hours orally, a santagesic 1 gram every 8 hours intravenously, and oxycodone intravenously with PCA. The second patient was given paracetamol tab 1 gram every 8 hours intravenously, analgesics 1 gram every 8 hours intravenously, and PCA intravenous oxycodone. Both patients felt the effectiveness of PCA as postoperative pain management. Conclusion: Multimodal analgesia or balanced analgesia is one method of managing acute postoperative pain. The success of using PCA is very much determined by the knowledge of the patient and the pain management team on PCA tools. Oxycodone provides fairly good analgesia with minimal side effects.